THE EFFECTIVENESS OF IMPLEMENTING THE ANDROID-BASED HIV CAR TOOLS APPLICATION TO LIFESTYLE CHANGES IN MOTHERS WITH HIV/AID - Meldawati Meldawati; Resi Galaupa (International Journal of Medicine and Health, 2023)
Background : Health is an indicator to measure the level of welfare of a society or nation. The current healthy paradigm being promoted requires a change in people's mindset from treating disease to maintaining or maintaining health so that you don't get sick, therefore an understanding of disease and how to prevent it needs to be disseminated to the community. One aspect of health at the end of the 20th century which was a disaster for humans was the emergence of a disease caused by a virus called HIV (Human Immunodeficiency Virus) which can cause AIDS (Acquired Immuno Deficiency Syndrome). Purpose of Writing : To find out the Effectiveness of Implementing the Android-Based HIV Care Tools Application for Lifestyle Changes in Mothers with HIV/AIDS at the Malingping Health Center in 2023. Research Methods : The type of research used was quantitative research. This research method is experimental with the type of Quasy Experimental (pseudo-experimental) with a one-group pretest-posttest design. This research was conducted at the Malingping Health Center in January-February 2023. The population in this study totaled 35 samples while the sample numbered 30 by means of sampling using purposive sampling. Research results : Output on the Chi Square Tests table, the calculated value of X2 = 38.830 with ap value = 0.000 <0.05 then Ho is rejected. So, it can be concluded that there is an effective relationship between the Implementation of the Android-Based HIV Care Tools Application on Lifestyle Changes in Mothers with HIV/AIDS. Conclusions and Suggestions: There is Application for Lifestyle Changes in Mothers with HIV/AIDS at the Malingping Health Center in 2023. It is hoped that the public will further increase their knowledge of the Care Tools program by actively participating in counseling given by related healthnworkes so that knowledge can be good and HIV transmission can be prevented.